A retrospective analysis of time delays in patients presenting with Cerebrovascular Accident (Stroke) - Khalema, Diteboho (My University, 2017)
Retrospective record review of time intervals regarding symptom onset, ED presentation and time to CT scan were recorded in patients who presented to the ED with signs and symptoms of stroke in 2014. RESULTS: There were 232 patient records included in the study. The average time to presentation to the ED was 33 hours with only 13.7% presenting within 3 hours. The earliest presentation was within 30 minutes of the onset of symptoms and the most delayed presentation was 3 months. Factors associated with early presentation were female sex, smoking and loss of consciousness. Known diabetic patients presented later than non-diabetic patients. Seventy-five percent of stroke patients had an ischaemic stroke and 25% were haemorrhagic. CONCLUSIONS: Due to delays in presentation, despite the availability of thrombolysis, patients are still not receiving thrombolytic treatment.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Medicine in Radiology.
Keywords: Radiography; Stroke; Emergency Service, Hospital